Determining the potential of institutionalizing larong Pinoy in public elementary schools in the Province of Rizal - De Jesus, Ermileen SD
This study attempts to assess the potential of institutionalizing the evolving Philippine games or Larong Pinoy to be a part of primary education curriculum, utilizing it as an educational tool. The assessment will focus on the collaboration of various related disciplines including Landscape Architecture. It relies on both a quantitative and qualitative approach to learn the viability of integrating it into public elementary education. The research jumpstarts by establishing a potential inclusion of various Larong Pinoy in innovative ways of teaching English, Science and Mathematics subjects in primary education. Then as a pilot study, existing facilities in different Rizal Province schools were selected and assessed of their outdoor capabilities to handle Larong Pinoy. At the end, guidelines and recommendations are to be formulated to establish the landscape design standards for the games-enhanced curriculum.